FF‐10832 enables long survival via effective gemcitabine accumulation in a lethal murine peritoneal dissemination model. Issue 9 (1st August 2019) - Higuchi, Tamami; Yokobori, Takehiko; Takahashi, Ryo; Naito, Tomoharu; Kitahara, Hiromu; Matsumoto, Takeshi; Kakinuma, Chihaya; Hagiwara, Shinji; Kuwano, Hiroyuki; Shirabe, Ken; Asao, Takayuki
Abstract: Chemotherapy has been the treatment of choice for unresectable peritoneal dissemination; however, it is difficult to eradicate such tumors because of poor drug delivery. To solve this issue, we developed FF‐10832 as liposome‐encapsulated gemcitabine to maintain a high concentration of gemcitabine in peritoneal tumors from the circulation and ascites. A syngeneic mouse model of peritoneal dissemination using murine Colon26 cell line was selected to compare the drug efficacy and pharmacokinetics of FF‐10832 with those of gemcitabine. Despite the single intravenous administration, FF‐10832 treatment enabled long‐term survival of the lethal model mice as compared with those treated with gemcitabine. Pharmacokinetic analysis clarified that FF‐10832 could achieve a more effective gemcitabine delivery to peritoneal tumors owing to better stability in the circulation and ascites. The novel liposome‐encapsulated gemcitabine FF‐10832 may be a curative therapeutic tool for cancer patients with unresectable peritoneal dissemination via the effective delivery of gemcitabine to target tumors. Abstract : Our nanotechnology achieved a surprising improvement of gemcitabine delivery to peritoneal tumors. FF‐10832 enabled the long‐term survival of lethal model mice, suggesting that it is a curative drug for cancer patients with unresectable dissemination. Furthermore, the ongoing phase I clinical trial will clarify the safety and efficacy of FF‐10832.